CO2 sorption on mesoporous solids: Effect of temperature and water content - Azmi, N. (American Chemical Society, 2017)
CO2 captured by solid adsorbents is considered one of the promising technologies for carbon capture and sequestration. The sorption equilibria of CO2 on commercial CO2 adsorbents (silica gel and Norit SX2) and synthesized CaO were measured experimentally by using a volumetric method in a temperature range of 0-8 °C, at which CO2 hydrate is stable to form. The CO2 uptake increases with decreasing temperature in silica gel and Norit SX2 on a dry basis; differs in CaO as the adsorption rate of CO2 in calciumbased sorbent is high at higher temperatures. The effect of water content on the samples studied was measured at a temperature of 2 °C on a wet basis. The highest CO2 amount adsorbed was obtained at the lowest value of water ratio studied (Rw = 0.03), which is close to CO2 sorption in a dry basis. However, the adsorption capacities on wet synthesized CaO were water-content dependent, of which the highest sorption capacity was obtained at a particular isotherm with a water ratio of 0.67. It can be concluded that CaO has the ability to be further utilized for CO2 separation in the presence of a minute quantity of water. © 2017 American Chemical Society.